Association of vaspin rs2236242 gene variants with type 2 diabetes and obesity in a Chinese population: A prospective, single‐center study. Issue 9 (20th February 2019) - Li, Ji; Li, Qian; Zhu, Ying‐Chun; Wang, Ya‐Kun; Gao, Cong‐Pu; Li, Xiao‐Ying; Ji, Tingting; Bai, Shou‐Jun
Abstract: Aim: Vaspin is an adipokine separated from visceral fat tissues of obese diabetic rats. This study was to investigate the association between vaspin rs2236242 gene polymorphism and type 2 diabetes mellitus (T2DM) or obesity in a Chinese population. Materials and Methods: T2DM patients and nondiabetic controls were recruited from Qingpu Branch of Zhongshan Hospital Affiliated to Fudan University (Shanghai, China) from May 1, 2015 to June 30, 2017. Clinicopathologic characteristics were recorded and their blood samples were collected. Serum vaspin levels were detected by enzyme‐linked immunosorbent assay and vaspin rs2236242 genotypes by tetra‐amplification refractory mutation system‐polymerase chain reaction. Results: Two hundred and ninety‐nine patients with T2DM and 311 controls were recruited at last. The vaspin genotypes of diabetic patients were distinct from nondiabetic controls ( χ 2 = 54.611, p < 0.0001). Genotyping revealed that T2DM patients have a greater prevalence of A allele compared with controls (61.9% vs. 42.1%, p < 0.0001). A allele was associated with an increased risk of T2DM (odds ratio = 2.23, 95% confidence interval = 1.773–2.804, p < 0.0001) compared with T allele. The genotype distribution did not differ among nondiabetic subjects with or without obesity. The serum vaspin levels were higher in T2DM patients and obese controls than the nonobese controls, however, the rs2236242 was not found to be significantly related to serum vaspin levels. Conclusions: Our findings showed the association between vaspin rs2236242 gene variants with obesity and T2DM in a Chinese population. People with rs2236242 A allele had a 2.23‐fold increased risk of T2DM. These findings suggest that vaspin rs2236242 may serve as a potential diagnostic and/or therapeutic targets for T2DM. Abstract : Our findings showed the association between vaspin rs2236242 gene variants with obesity and type 2 diabetes mellitus (T2DM) in a Chinese population. People with rs2236242 A allele had a 2.23‐fold increased risk of T2DM. These findings suggest that vaspin rs2236242 may serve as a potential diagnostic and/or therapeutic targets for T2DM.